Maintenance of xylem Network Transport Capacity: A Review of Embolism Repair in Vascular Plants - Brodersen, Craig; McElrone, Andrew (Frontiers in Plant Science, 2013)
Maintenance of long distance water transport in xylem is essential to plant health and productivity. Both biotic and abiotic environmental conditions lead to embolism formation within the xylem resulting in lost transport capacity and ultimately death. Plants exhibit a variety of strategies to either prevent or restore hydraulic capacity through cavitation resistance with specialized anatomy, replacement of compromised conduits with new growth, and a metabolically active embolism repair mechanism. In recent years, mounting evidence suggests that metabolically active cells surrounding the xylem conduits in some, but not all, species are capable of restoring hydraulic conductivity. This review summarizes our current understanding of the osmotically driven embolism repair mechanism, the known genetic and anatomical components related to embolism repair, rehydration pathways through the xylem, and the role of capacitance. Anatomical differences between functional plant groups may be one of the limiting factors that allow some plants to refill while others do not, but further investigations are necessary to fully understand this dynamic process. Finally, xylem networks should no longer be considered an assemblage of dead, empty conduits, but instead a metabolically active tissue finely tuned to respond to ever changing environmental cues.